Evidence For Signaling From The Center Of The Immune Synapse - Čemerski, Sašo (2008)
The role of the immune synapse, and in particular the role of the central region of the synapse (the central supramolecular activation cluster or cSMAC), is controversial. One model suggests that the sole function of the cSMAC is to downregulate receptors and turn off signaling and that TCR signaling occurs only in the pSMAC. A second model suggests that the role of the cSMAC depends on antigen quality and can both enhance signaling and receptor downregulation. Here, we provide evidence that while at early time points signaling occurs mainly outside the cSMAC, at later time points signaling does occur in the cSMAC. Additionally, we find that cSMAC formation can increase the stimulatory potency of weak agonists for the TCR. Combined with previous studies showing that cSMAC formation decreases the stimulatory potency of strong agonists, our data support a model that posits that signaling and receptor degradation are linked in the cSMAC and that the balance between signaling and degradation in the synapse is determined by antigen quality.